PENGARUH SPIRITUALITAS DI TEMPAT KERJA TERHADAP KOMITMEN ORGANISASIONAL DENGAN KESEJAHTERAAN PEGAWAI SEBAGAI VARIABEL INTERVENING - Abdul Kholid; Siti Nurmayanti; Akhmad Saufi (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
Organizational commitment is an important thing for every employee in an organization to achieve the vision of the agency. This is because with the organizational commitment possessed by employees, it can help the organization to achieve the goals that have been set. This study aims to analyze whether spirituality in the workplace has an influence on organizational commitment and employee welfare, and whether employee welfare can be a mediating variable between spirituality in the workplace and organizational commitment. This research uses explanatory research method. The sample used in this study were 34 employees of the Ministry of Religion of East Lombok Regency. The analysis technique used is Partial Least Square (PLS). The results of the study show that: (1) Spirituality in the workplace has a positive and significant effect on organizational commitment, (2) Spirituality in the workplace has a positive and significant effect on employee welfare. Employee welfare has a positive and insignificant effect on organizational commitment, (3) Employee welfare mediates the effect of Spirituality in the Workplace on Organizational Commitment in employees of the Office of the Ministry of Religion of East Lombok Regency.